A Composite Renal Tumor with Dual Differentiation, Chromophobe and Collecting Duct Carcinoma - Lauren Pearson; Douglas J. Taatjes; Michele von Turkovich; Benjamin J. King; Maryam Zenali (Case Reports in Pathology)
Chromophobe carcinoma constitutes a small subset of all renal carcinomas. Within this category, rare tumors with divergent differentiation have been recognized. Herein, we report a rare case of composite chromophobe and collecting duct carcinoma and describe its pathologic and clinical features.